An Investigation On The Aetiology Of Plague -Like Disease In Ducks In Kerala - Krishnan Nair G (Department of Microbiology, College of Veterinary and Animal Sciences, 1978)
An investigation was carried out to isolate, characterize and identify the agent responsible for the outbreak of duck plague – like disease in ducks in Kerala. Specimens (liver and spleen) from field cases, were processed for virus isolation and were inoculated into either developing duck or chick embryos, by chorio – allantoic (C.A.M.) or allantoic cavity method. Virus isolation was possible only by C. A. M. inoculation of duck embryos and was confirmed by inoculation of the C.A.M. extracts into duck embryo fibroblast (D.E.F.) cell cultures. The cytopathic changes produced by the field isolate DPV – N; its physico – chemical characteristics such as sensitivity to chloroform and 5 – iodo – 2 deoxyuridine; and the effect of exposure to various pH values such as 4.7, 7.2 and 9.1, were compared with that of a known duck plague virus DPV – K, received from the Veterinary Biological Institute, Mannuthy. In D.E.F. cell cultures, the cytopathic changes produced by DPV – N and DPV – K were rounding and clumping of cells, with characteristic basophilia and granulation of the cytoplasm. Although the initial titers of both DPV - N and DPV - K were only 105 and 106.25, they increased to 107.5 and 108.25 respectively, on further passages. The field isolate DPV – N and the known duck plague virus DPV – K were sensitive to 5% chloroform, with complete inactivation in ten minutes. Similarly, both the strains failed to multiply and produce cytopathis changes in cells treated with IUdR, at the rate of 100 micrograms per ml. However, differences were observed in their thermostability and pH sensitivity. Although DPV – K was inactivated completely at 560 C. in 30 minutes, DPV – N was only partially reduced in titer. DPV – N was also found to be resistant, when both the strains were exposed to pH 4.7, for a period of four hours at room temperature. But both were unaffected at pH 7.2 and got inactivated at pH 9.1. Both the strains also failed to produce any haemagglutination reaction with chicken R.B.C or precipitation reaction in agar gels. Although duck plague specific antiserum neutralized homologous strain DPV – K and the newly isolated strain DPV – N, the serum titers obtained with the latter was only less. Experimental infection studies have shown that one to six week – old ducklings were equally susceptible to DPV – N and DPV- K, either with the spleen extract or with tissue culture passaged sample. The symptoms and lesions produced in both cases, were similar to those described for duck plague and also to those seen during the disease outbreak in Kerala. The virus that caused an outbreak of duck plague - like disease in Kerala is found to be indistinguishable from that of duck plague. It is also strongly felt that the lack of complete protection of birds vaccinated with duck plague vaccine is due to t possible strain variation between the classical duck plague virus DPV – K and the virus as it occurred during this outbreak. However, it needs thorough in vitro cross neutralization and in vivo cross protection tests before any definite conclusions can be made on the strain variation of duck plague virus.